space to grow: copyright, cultural policy and commercially focused music in china - Montgomery, Lucy (Routledge, 2009)
A difficult copyright environment, combined with the Chinese government's continuing power over key distribution and promotion channels, including radio, television, publishing and concerts (Baranovitch, 2003 ; Brady, 2006 ), have been key factors in the failure of international labels to secure a dominant position in China's rapidly developing domestic music market. This paper argues that while international record labels have been paralyzed by concepts of value that depend on an ability to control the copying of music products and to enforce intellectual property rights (Montgomery & Potts, 2008 ), domestic music and entertainment businesses are actively exploring strategies that allow them to function in a weak copyright environment. Cultural policies ostensibly intended to prevent the circulation of heterodox content are having an important side‐effect: making it more attractive for music‐related businesses to promote and distribute local content. As a result, domestic music and entertainment businesses are developing a distinct advantage in the highly competitive Chinese market.